Ontological Knowledge for Goal-Driven Autonomy Agents in Starcraft - Dannenhauer, Dustin (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2013)
Starcraft, a commercial Real-Time Strategy (RTS) game that has enjoyed world-wide popularity (including televised professional matches), is a challenging domain for automated computer agents. Evidence of this difficulty comes not only from characteristics of the game (massive state space, stochastic actions, partial visibility, etc.) but also from three years of competitive entries in tournaments (i.e. AIIDE Annual Starcraft Competition) in which the best automated entry performs poorly against a human expert. We are interested in taking a new research direction: using semantic knowledge, such as description logic, to represent the game state with abstract concepts in order to perform high level actions.